THE EFFECT OF ACCOUNTING UNDERSTANDING, INFORMATION TECHNOLOGY, AND INTERNSHIP EXPERIENCE ON JOB READINESS AS AN ACCOUNTANT IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 AND SOCIETY 5.0 - Radina Rima Ananda; Fadilla Purwitasari; Ricky Angga Ariska (Journal of Artificial Intelligence and Digital Economy, 2024)
The purpose of this study is to ascertain how an individual's knowledge of accounting, IT usage, and internship experience affect their preparedness for the workforce in the 4.0 and 5.0 industrial revolutions. This study employs a quantitative methodology. Thirty samples were gathered using the purposive sampling method based on the non-probability sampling technique. Multiple linear regression analyses were used in the data processing procedure. The findings of the study indicate that having an internship, using information technology, and having a basic Accounting Understanding all have a positive and significant impact on one's fitness for the workforce as an accountant in the context of the Industrial Revolution 4.0 and Society 5.0. Thus, an individual's degree of work preparedness can be influenced by their knowledge of accounting, their proficiency with information technology, and their internship experience.